The effects of splinting periodontally compromised removable partial denture abutments on bone stresses: a three-dimensional finite element study - Allahyar Geramy; Mehdi Adibrad; Mahasti Sahabi (Elsevier, 2010)
Periodontally compromised abutments complicate the treatment plan of distal extension removable partial dentures. The objectives of this study were: (1) to determine if splinting a tooth with reduced bone height to a healthy one is beneficial to the weak one; (2) to investigate fixed splinting of two teeth (the first and second premolars) with various alveolar support levels on bone stress around the periodontal construction according to different crown to root ratios of the periodontally compromised abutment; and (3) to assess the efficiency of splinting in the presence of non-axial loads. Materials and methods: Thirteen three-dimensional finite element models were designed that included the mandibular first and second premolars and the surrounding bone. Ten models were similar except for the alveolar bone height around the second premolar that had different amounts of bone resorption of 0-9 mm with splinted teeth. The last three were the same except for the teeth which were not splinted. A vertical force of 25 N was applied to each occlusal surface of the premolars. Finally, von Mises stress was evaluated at three points for all models. In the first stage, the efficiency of splinting was assessed. In the last stage, the effects of non-axial loads were evaluated in the splinted teeth models. Results: In stage 1, it was shown that splinting could redirect the stresses to apical areas and prevented crestal bone from increased stress. In stage 2, the findings of von Mises stress in the apical area of the first premolar were almost the same in all models. In the apical area of the second premolar and the alveolar crest area, the bone stress increased when the height of the alveolar bone of the second premolar decreased. Stage 3 revealed that splinted teeth are efficient in carrying non-axial loads. Conclusion: Splinting a very weak abutment to an adjacent healthy tooth might not be beneficial. The acceptable crown to root ratio for fixed splinting a weak abutment to an adjacent normal tooth was around 1.65-2.